OPTIMASI SEDIAAN FLOATING TABLET RANITIDIN MENGGUNAKAN KOMBINASI MATRIKS KITOSAN DAN HPMC - Mahardika, Yoga Chandra; , Erindyah R. Wikantyasning, Ph.D., Apt (2017)
Tablets were made with floating systems to prolong residence time in the stomach and controlling drug release. Drugs used in the study were ranitidine with a combination of matrix is HPMC K4M and chitosan for making tablet density lower than gastric acid, chitosan also has mucoadhesive properties which is non-toxic, biodegradable and biocompatible. The purpose of this research is to know the effect of HPMC K4M matrix combination and chitosan on physical properties, dissolution profile and obtain optimum formula on tablet floating ranitidine. Tablets were made with a various combination of HPMC K4M matrix and chitosan by comparison F1 (33.33%: 66.66%), F2 (41.66%: 58.33%), F3 (50%, 50%), F4 (58.33%: 41.66%) and F5 (66.66%: 33.33%). Evaluation of granules and tablets performed using granule test (flow rate, the angle of repose, tapped density), physical test of tablet (weight uniformity, hardness, friability, lag time and floating time and dissolution). From those data, obtained the optimum formula and then verification data analyzed by using One-Simple T-Test. The results obtained in the optimum formulation with the combination of 36% chitosan and 64% HPMC K4M after the statistic test which have the parameters of flow rate, the angle of repose, tapped density, weight uniformity, hardness, friability, lag time and floating time show the difference is not significant so the data is valid. In the dissolution test parameter results show the difference is significant but the results of the paremeter are